1991
DOI: 10.1042/bj2800533
|View full text |Cite
|
Sign up to set email alerts
|

A high-affinity inositol 1,3,4,5-tetrakisphosphate receptor protein from brain is specifically labelled by a newly synthesized photoaffinity analogue, N-(4-azidosalicyl)aminoethanol(1)-1-phospho-d-myo-inositol 3,4,5-trisphosphate

Abstract: A photolabile arylazido analogue of Ins(1,3,4,5)P4 selectively substituted at the 1-phosphate group was synthesized by coupling 2-aminoethanol(1)-1-phospho-D-myo-inositol 4,5-bisphosphate with N-hydroxysuccinimidyl-4-azidosalicylic acid [Schäfer, Nehls-Sahabandu, Grabowsky, Dehlinger-Kremer, Schulz & Mayr (1990) Biochem. J. 272, 817-825] and subsequently phosphorylating the product by bovine brain Ins(1,4,5)P3 3-kinase. The product, N-(4-azidosalicyl)-aminoethanol(1)-1-phospho-D-myo-inositol 3,4,5-trisphosphat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…We identified a different InsP4 receptor protein, the 42 kDa neural protein which we purified to homogeneity from cerebellum from several species (DoniC and Reiser, 1991;Reiser eta/., 1995a). Moreover, we recently found that the purified native receptor protein from porcine cerebellum recognizes not only InsP4 (G 2.2 nM) but also the water soluble analogue of phosphatidylinositol-(3,4,5)-trisphosphate (PtdInsP3) glycero-phosphatidylinositol-( 3,4,5)-trisphosphate with the same high affinity (Stricker et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…We identified a different InsP4 receptor protein, the 42 kDa neural protein which we purified to homogeneity from cerebellum from several species (DoniC and Reiser, 1991;Reiser eta/., 1995a). Moreover, we recently found that the purified native receptor protein from porcine cerebellum recognizes not only InsP4 (G 2.2 nM) but also the water soluble analogue of phosphatidylinositol-(3,4,5)-trisphosphate (PtdInsP3) glycero-phosphatidylinositol-( 3,4,5)-trisphosphate with the same high affinity (Stricker et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Other inositol phosphates such as Ins(1,3,4,5)P % and InsP ' are found in many cells, and it has been suggested that they are also involved in signal transduction processes, including the control of cytosolic Ca# + levels and clathrin assembly, but their specific functions are largely either unclear or unknown. InsP % is formed intracellularly by the phosphorylation of InsP $ , and InsP % binding sites have been identified in cerebellum [1,2], HL-60 cells [3], adrenal cortex [4], liver [5] and platelets [6]. A specific InsP % receptor has been purified from pig platelet plasma membranes [7], and recently its cDNA was sequenced and shown to code for a member of the GTPase-activating protein (GAP) protein family, and designated as GAP1 IP%BP [8].…”
Section: Introductionmentioning
confidence: 99%
“…have recently purified a pH 5.0-dependent Ins(1,3,4,5)P4 binding protein from pig cerebellum which appears to be a single protein of 42 kDa molecular mass. Further to this, Reiser et al (1991) have recently developed an Ins(1,3,4,5)P4 photoaffinity analogue which, when used to probe pig cerebellum under acidic conditions, binds specifically to a 42 kDa protein. In apparent contradiction to this, Theibert et al (1991) have described and purified rat cerebellar proteins which bind Ins(1,3,4,5)P4 at pH 7.4-8.3.…”
Section: Introductionmentioning
confidence: 99%